Pancasila sebagai Moral Foundation dalam Pencegahan Korupsi di Indonesia - Nadhifah, Mizda Jauharotun (Maliki Interdisciplinary Journal, 2026)
This article discusses the role of Pancasila as a moral foundation in efforts to prevent corruption in Indonesia. Corruption is not only considered a legal deviation, but also a failure of public ethics that arises from weak integrity, morality, and responsibility among officials and citizens. The values of Pancasila are then positioned as the foundation of national ethics that can guide anti-corruption behavior. Through an analysis of the values of each principle, this article shows that the principles of belief in God, humanity, unity, deliberation, and justice are closely related to the formation of an anti-corruption character. The implementation of these values is reinforced through Pancasila education and anti-corruption education from an early age, as a way of instilling deep moral values. However, challenges arise due to the declining relevance of Pancasila among the younger generation and a weak understanding of these values. Therefore, strengthening the ethics of state administrators is an important step in realizing Pancasila in bureaucratic practices and public services. Overall, this article emphasizes that preventing corruption requires a moral approach based on Pancasila that encompasses education, culture, and government ethics.